Generations on the land : a conservation legacy - Patoski, Joe Nick, 1951- (Texas A & M University Press, 2010)
The landowners in this book have improved their land and done so by being profitable, generous to their human community, committed to family, and desirous of leaving land better than when it came into their stewardship.-from the introduction by Brent Haglund In 2008, the Sand County Foundation and the Texas.